2021
DOI: 10.1292/jvms.20-0617
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Blatticola blattae</i> (Thelastomatidae) in German cockroaches <i>Blattella germanica</i> in Japan

Abstract: A survey for nematode infection in German cockroaches captured in restaurants in various areas of Japan as well as the laboratory-bred colony was carried out. The nematodes were then identified morphologically and molecularly. Of the 320 German cockroaches collected at 79 restaurants in 26 prefectures in Japan, 66.6% (213/320) were found to be parasitized by a single species of pinworm in the hindgut. The mean number of pinworms per cockroach was less than 1.6. Of the three laboratory-bred lines of cockroaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The German cockroach is an important sanitary insect pest that is widely found in urban human living spaces worldwide. In addition, numerous studies have indicated that B. blattae is a common nematode parasite of the German cockroach (Adamson and Waerebeke 1992;Jarry 1964;Tsai and Cahill 1970;Kobayashi et al 2021). The results of the present study suggest that B. blattae infection enhances the survival of German cockroaches.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The German cockroach is an important sanitary insect pest that is widely found in urban human living spaces worldwide. In addition, numerous studies have indicated that B. blattae is a common nematode parasite of the German cockroach (Adamson and Waerebeke 1992;Jarry 1964;Tsai and Cahill 1970;Kobayashi et al 2021). The results of the present study suggest that B. blattae infection enhances the survival of German cockroaches.…”
Section: Discussionsupporting
confidence: 65%
“…The German cockroach, Blattella germanica, is frequently infected with the pinworm, Blatticola blattae (Kobayashi et al 2021). Although pinworm infection is common among cockroaches worldwide, few reports have described the effects of parasite infection on the insect host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement and trade of animals, fruits, vegetables, and other products within the market premises allow the introduction and dissemination of these parasites. In a study conducted by Amawulu et al in Yenagoa Metropolis, Nigeria, the researchers found that helminth eggs contaminate the fruits purchased in public markets, with Ascaris lumbricoides being one of the intestinal parasite species recovered on fruits (Kobayashi et al, 2020) . This aligns with the study conducted by Vizon et al in 2019, which revealed that Ascaris lumbricoides and Hookworm contaminate green-leafy vegetables such as cabbage, lettuce, and Chinese cabbage sold in public markets in Nueva Ecija, Philippines.…”
Section: Resultsmentioning
confidence: 99%
“…Thelastomatoids live in the hindgut of the host and usually feed upon the gut microfauna. Thelastomatoids have been studied in many countries and regions around the world [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Adamson and van Waerebeke [2] diagnosed 27 genera and provided a list of 174 species in the family, Thelastomatidae.…”
Section: Introductionmentioning
confidence: 99%